PENGARUH PEMBERIAN EKSTRAK ETANOL DAUN RAMBUSA (Passiflora foetida Linn) TERHADAP KADAR KREATININ DALAM DARAH TIKUS WISTAR JANTAN - Evi Mulyani; Halida Suryadini; Aditama Reyhan (Jurnal Insan Farmasi Indonesia, 2022)
Rambusa (Passiflora foetida, Linn) is one of the plants that empirically has potential as a medicine that has been used by the people of Central Kalimantan. Rambusa is reported to have many medicinal properties, one of which is anti-diabetic. In addition to its potential as a medicine, the Rambusa plant with its diversity of ingredients also has the potential to be detrimental to the body both at the cellular level and even organs that function vitally such as the kidneys. The aim of the study was to describe the kidney function of Wistar rats after administration of ethanol extract of the leaves of the Rambusa. The method in this study was carried out in vivo in male Wistar rats with serum creatinine (Scr) as a parameter of kidney function. The extract was given orally at doses of 1 mg/kg, 1.5 mg/kg, and 2 mg/kg and 2,5 mg/kgBB, respectively. each group for 7 (seven) days. The results showed that Scr levels were still within normal limits, namely between 0,578-1,128 mg/dl, and there was no significant difference between the control group and the treatment group.